2016
DOI: 10.1111/brv.12298
|View full text |Cite
|
Sign up to set email alerts
|

Wolf population genetics inEurope: a systematic review, meta‐analysis and suggestions for conservation and management

Abstract: The grey wolf (Canis lupus) is an iconic large carnivore that has increasingly been recognized as an apex predator with intrinsic value and a keystone species. However, wolves have also long represented a primary source of human-carnivore conflict, which has led to long-term persecution of wolves, resulting in a significant decrease in their numbers, genetic diversity and gene flow between populations. For more effective protection and management of wolf populations in Europe, robust scientific evidence is cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
138
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 172 publications
8
138
1
3
Order By: Relevance
“…Hindrikson et al. () showed that the genetic diversity of wolf populations in Europe could be influenced by other populations up to 850 km away, suggesting differentiation of the wolf populations at a large scale. However, our results show that the northern Iberian wolf population could display differentiation at very much smaller scales in line with observations of Finnish wolves (Aspi, Roininen, Ruokonen, Kojola, & Vilà, ; Aspi et al., ), which indicate average dispersal distances of about 100 km and significant population differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Hindrikson et al. () showed that the genetic diversity of wolf populations in Europe could be influenced by other populations up to 850 km away, suggesting differentiation of the wolf populations at a large scale. However, our results show that the northern Iberian wolf population could display differentiation at very much smaller scales in line with observations of Finnish wolves (Aspi, Roininen, Ruokonen, Kojola, & Vilà, ; Aspi et al., ), which indicate average dispersal distances of about 100 km and significant population differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only shallow regional genetic structure has been detected among several mammal species occurring across northern Eurasia (e.g. Hindrikson et al., ; Korsten et al., ). However, that emerging picture is by no means definitive, as these comparisons were made using relatively short mitochondrial sequences (Davison et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This is a case of anthropogenic hybridization (i.e., the interbreeding of individuals from genetically distinct populations due to human action; Allendorf et al., ) and is considered a major threat to wolf genomic integrity (Boitani, ). Therefore, accurately estimating the prevalence of hybrids in wolf populations is a priority to elaborate conservation strategies (Hindrickson et al, ). We show that in this case using naive prevalence as a proxy underestimates the prevalence of hybrids.…”
Section: Introductionmentioning
confidence: 99%